Elaboração de testes de desempenho do tipo caixa preta para a funcionalidade de reserva de espaços do sistema de agendamento do Campus de Castanhal - ASSIS, Eduardo Bernardo da Silva de (2022)
This work aims to study and the elaboration of automated black box performance tests for the space reservation functionality of the campus locations scheduling system, highlighting the use of the open source tool Jmeter. The results of the tests performed indicate that the number of simultaneous requests that the system supports are around 200 requests, which was considered satisfactory by the daily averages of demand that the system receives.